2006
DOI: 10.1016/j.clpt.2006.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Potent cytochrome P450 2C19 genotype–related interaction between voriconazole and the cytochrome P450 3A4 inhibitor ritonavir

Abstract: Coadministration of a potent CYP3A4 inhibitor leads to a higher and prolonged exposure with voriconazole that might increase the risk of the development of adverse drug reactions on a short-term basis, particularly in CYP2C19 PM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 36 publications
8
113
1
Order By: Relevance
“…Mean plasma concentration-time profile of the metabolites OH-voriconazole and DiOH-voriconazole after oral (open symbols) and intravenous (closed symbols) administration of a single 400 mg dose of voriconazole to 20 healthy participants participants compared with EM is similar to the previously reported differences observed after oral administration [3,4,6,9].To switch from the i.v. to oral route of administration without dose adjustment is possible in general due to the high bioavailability of all CYP2C19 genotypes.…”
Section: Figuresupporting
confidence: 72%
See 1 more Smart Citation
“…Mean plasma concentration-time profile of the metabolites OH-voriconazole and DiOH-voriconazole after oral (open symbols) and intravenous (closed symbols) administration of a single 400 mg dose of voriconazole to 20 healthy participants participants compared with EM is similar to the previously reported differences observed after oral administration [3,4,6,9].To switch from the i.v. to oral route of administration without dose adjustment is possible in general due to the high bioavailability of all CYP2C19 genotypes.…”
Section: Figuresupporting
confidence: 72%
“…Because these enzymes are responsible for the main metabolic pathways of many drugs, there is a considerable potential for drug interactions, including both inhibition and induction of voriconazole metabolism by other drugs. Indeed, inhibition of voriconazole metabolism by omeprazole [1,5] or ritonavir [6] and induction by phenytoin [7] or St John's wort [8] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Coadministration of drugs with strong inhibitory effects on CYP3A4, such as ritonavir, a human immunodeficiency virus protease inhibitor, prevents metabolism of voriconazole by CYP3A4 enzymes and thereby leads to higher voriconazole concentrations with the risk of increased adverse events such as hepatotoxicity. 9 Indeed, hepatotoxicity is a dose-limiting adverse event in patients taking voriconazole, which is often observed. Moreover, clinically significant hepatic dysfunction occurs in more than 10% of patients receiving regular doses of voriconazole and is a major cause of discontinuation of this drug.…”
Section: Discussionmentioning
confidence: 99%
“…Among the drugs which are metabolized by CYP2C19 enzymes are cytostatics, proton pump inhibitors, antidepressants, sedative, beta blockers, antiviral and anti-fungal agents. [2][3][4][5][6][7][8][9] Recently, it was demonstrated that PMs of CYP2C19 showed a decrease in platelet responsiveness to clopidogrel. 10 In another study, it was reported that patients treated with antidepressants and genotyped as PMs for CYP2D6 and CYP2C19, remained in hospital for longer (median 57.5 versus 40.0 days) compared to IMs.…”
Section: Introductionmentioning
confidence: 99%
“…69 Interestingly, the coexistence of multiple CYP polymorphisms in the same patient do not necessarily have an additive effect on the metabolism of voriconazole. [70][71][72] Metabolism of voriconazole results in several metabolites, the major circulating metabolite being the N-oxide of voriconazole, 65 formed predominantly by CYP3A4 and 2C19, with a smaller contribution from 2C9. 73 Production of the methyl hydroxylated metabolite is due solely to CYP3A4.…”
Section: Anidulafunginmentioning
confidence: 99%